2009
DOI: 10.1063/1.3075907
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy-type defects in Mg-doped InN probed by means of positron annihilation

Abstract: The introduction of vacancy-type defects into InN by Mg-doping was studied using a monoenergetic positron beam. Doppler broadening spectra of the annihilation radiation were measured for Mg-doped InN (N-polar) grown on GaN/sapphire templates using plasma-assisted molecular beam epitaxy. The concentration of In-vacancy (VIn) related defects was high near the InN/GaN interface, and the defect-rich region expanded from the interface toward the surface with increasing Mg concentration [Mg]. Using electrolyte-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…V In -mV N , in accordance to what has been proposed earlier in Mg-doped InN. 20 Based on the TEM data, the observed increase in vacancy clustering at the InN/Gan interface coincides with elevated dislocation densities in that area. In order to assess the effect of dislocations on the formation energies of point defects in their vicinity, we performed DFT calculations of strained InN lattices.…”
Section: à2supporting
confidence: 90%
“…V In -mV N , in accordance to what has been proposed earlier in Mg-doped InN. 20 Based on the TEM data, the observed increase in vacancy clustering at the InN/Gan interface coincides with elevated dislocation densities in that area. In order to assess the effect of dislocations on the formation energies of point defects in their vicinity, we performed DFT calculations of strained InN lattices.…”
Section: à2supporting
confidence: 90%
“…Similar behavior of the S values was also observed for In x Ga 1-x N, and this is typical for group-III nitride films grown by heteroepitaxial growth. 29,30,32 The observed SÀE curves were fitted using Eq. shown.…”
Section: Methodsmentioning
confidence: 99%
“…30,34 Positron annihilation studies of N-polar InN:Mg identified nitrogen vacancy clusters for Mg concentrations below 2 Â 10 19 cm À3 while for Mg concentrations above the p-type window (when the conductivity is switched to n-type again) complexes between indium vacancy and nitrogen vacancy clusters were found. 35 Recently, Choi et al 36 reported on the degradation of surface morphology and onset of polarity inversion for Mg concentration above 7 Â 10 19 cm À3 . It has also been found that zinc-blende (ZB) InN is formed when Mg concentration exceeds 1.8 Â 10 20 cm À3 (Ref.…”
Section: Introductionmentioning
confidence: 99%